2013
DOI: 10.1016/j.pupt.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

AP301, a synthetic peptide mimicking the lectin-like domain of TNF, enhances amiloride-sensitive Na+ current in primary dog, pig and rat alveolar type II cells

Abstract: Pulmonary permeability oedema is a frequent complication in a number of life-threatening lung conditions, such as ALI and ARDS. Apart from ventilation strategies, no specific therapy yet exists for treatment of these potentially fatal illnesses. The oedema-reducing capacity of the lectin-like domain of TNF (TIP) and of synthetic peptides, mTIP and hTIP, which mimic the TIP domain of mouse and human TNF, have been demonstrated in various studies in rodents. Cell-based electrophysiological studies have revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…In previous studies, our research group and other investigators have demonstrated that the lectin-like domain of TNF represents a potent stimulator of ALC in several mammalian species and involves activation of ENaC via an unknown mechanism (21,24,(27)(28)(29)(30)(31)38) . This study was designed to determine the mechanism by which the lectin-like domain of TNF can promote ENaC activity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous studies, our research group and other investigators have demonstrated that the lectin-like domain of TNF represents a potent stimulator of ALC in several mammalian species and involves activation of ENaC via an unknown mechanism (21,24,(27)(28)(29)(30)(31)38) . This study was designed to determine the mechanism by which the lectin-like domain of TNF can promote ENaC activity.…”
Section: Discussionmentioning
confidence: 92%
“…Because both Na (29) and ENaC (27,28,38) can be activated by the TIP peptide, we investigated in more detail which of these Na 1 transporters is the primary target in a homologous cell system and whether the peptide has a direct or indirect effect on their activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current-enhancing effect of AP301 is not inhibited by CNG channel blockers, suggesting that AP301 activates Na 1 current flowing through ENaC (Tzotzos et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…AP301 [Cyclo(CGQRETPEGAEAKPWYC)], a cyclic peptide comprising the human TIP sequence and currently being developed as a treatment for lung edema (phase II clinical trials), has been shown to reduce extravascular lung water and improve lung function in a pig model of acute lung injury (Hartmann et al, 2013) and to enhance the amiloride-sensitive Na 1 current in freshly isolated ATII cells from dog, pig, and rat lungs (Hamacher et al, 2010;Tzotzos et al, 2013). The current-enhancing effect of AP301 is not inhibited by CNG channel blockers, suggesting that AP301 activates Na 1 current flowing through ENaC (Tzotzos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%